Alternative Approaches To the Spectral Quantitative Resolution of Two-Component Mixture by Wavelet Families - Dinc, Erdal; Baleanu, Dumitru; Arslan, Fahrettin; Baleanu, Dumitru (Soc Chilena Quimica, 2009)
A new spectral continuous wavelet transform (CWT) methods are proposed for the quantitative analysis of the binary mixtures. The simultaneous spectral resolution of binary mixtures and tablets containing paracetamol (PAR) and chloroxozone (CHL) with overlapping absorption spectra is performed by six wavelet families with no chemical separation procedure. The calibration graphs for the six wavelet families are obtained by the help of the data collected from the CWT-signal amplitudes corresponding to the zero crossing points in the spectral range of 210 nm-310 nm. The validation of each wavelet family is carried out by analyzing various synthetic binary mixtures of the above mentioned drugs. The second derivative spectrophotometry (D2) is used to compare the experimental results provided by the analyzed continuous wavelet families and a good coincidence is reported for the proposed analytical approaches.
Alternative approaches to the spectral quantitative resolution of two-component mixture by wavelet families
Keywords: Continuous Wavelet Families; Simultaneous Determination; Paracetamol; Chloroxozone; Binary Mixture; Tablets